Adaptasi Revised-Multidimesional Scale of Perceived Social Support pada Guru di Kota Bandung - Oktarina, Tri Dini; Cahyadi, Surya; Susanto, Hery (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to test the reliability and validity of the Revised Multidimensional Scale of Perceived Social Support (R-MSPSS) which has been translated to bahasa Indonesia. This study uses a quantitative approach. Data was obtained from 285 teachers in Bandung (include elementary school, junior high school, and high school) who implemented distance learning during the Covid-19 pandemic. The sampling technique used was convenience sampling. Â The data were collected using a questionnaire in the form of google form that was distributed through social media. The data analysis techniques in this study was an internal consistency test using Cronbachâ€™s alpha to calculate the reliability of the instrument and confirmatory factor analysis with diagonally weighted least square estimation to prove construct validity using the JASP version 0.14 program. The results of this study indicate that the R-MSPSS has good reliability with the Cronbach's alpha value on the total score and the score for each dimension of more than 0,7. The result of factor confirmatory analysis shows that the R-MSPSS model with 4 factors is in accordance with the measured construct. The results of this study indicate that the R-MSPSS is a reliable and valid instrument for measuring teachers' perceived social support.